Moriscos and Their Political Life in Andalusia and Morocco (908-1007 AH/1502-1598 AD) - Khwaiter , Marwan Ahmed; Bashinah, Mohammed Omar (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
The study of the Moriscos constitutes a vital and significant aspect of the political، social، and religious history of Al-Andalus. This topic is fundamental for understanding the cultural and civilizational heritage of Andalusia. Despite its importance، it has not received sufficient attention due to its relative historical novelty. However، this field demonstrates a significant impact and interaction with other cultures. The aim of studying the Moriscos is to uncover the extent of their connection to political، social، and religious life in Al-Andalus. The study also reveals the level of hostility they faced from the Spanish state. It seeks to document their history within the realms of politics، society، and religion. The study employs a historical methodology based on analysis، inference، description، and extrapolation. Among the key findings of the study: The Moriscos are the result of intermarriage between Arabs and Spaniards. They experienced wars initiated by the Spanish، leading to their migration to Morocco. Additionally، the Moriscos interacted harmoniously with the inhabitants of Morocco across various aspects.